Determination of the full deformation tensor by multi‐Bragg fast scanning nano X‐ray diffraction. Issue 1 (7th January 2020) - Johannes, Andreas; Rensberg, Jura; Grünewald, Tilman A.; Schöppe, Philipp; Ritzer, Maurizio; Rosenthal, Martin; Ronning, Carsten; Burghammer, Manfred
Abstract : A method for determining the full deformation tensor from a scanning nano X‐ray diffraction experiment mapping two Bragg peaks is described. Abstract : This work showcases a method to map the full deformation tensor in a single micro‐sized crystal. It is shown that measuring the position of two Bragg reflections in reciprocal space is sufficient to obtain the full deformation tensor, if the condition of incompressibility of the material is imposed. This method is used to reveal the surface tension induced deformation at the edges of an as‐grown single‐crystal VO2 microwire. All components of the deformation tensor of the microwire were measured down to an absolute value of 10 −4 in an 8 × 14 µm projected area of the wire. With a beam‐defined spatial resolution of 150 × 150 nm, the measurement time was merely 2.5 h.